Implementing data analytics and architectures for next generation wireless communications - Bhatt, Chintan M., 1988-; Kumar, Neeraj (Computer scientist); Bashir, Ali Kashif, 1982-; Alazab, Mamoun, 1980- (Advances in wireless technologies and telecommunication (AWTT) book series., 2022)
"This book covers the existing and emerging theoretical and practical challenges in the design, development and implementation of big data algorithms, protocols, architectures, and applications for next-generation wireless communications and their applications in smart cities"--